Problems of Teacher Education in India: Addressing the Challenges in Teacher Education in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Education plays an extremely critical part in fostering a person to the degree of flawlessness by drawing out the best resident from him, best Indian from him. Education is a deep rooted measure and without the assistance of a teacher it will be inadequate. Teacher readiness has been a topic of conversation at all levels, from the public authority, services, administrative bodies, schools, to teachers themselves. No country creates past the nature of its education framework, which is profoundly reliant upon the nature of its teachers. A few problems are tormenting the arrangement of teacher education so the teachers ought to be given the most proper instruments during and after their preparation, including content information and abilities just as helping philosophy to have the option to tackle their job expertly. This full length paper featured the serious problems and a few ideas to settle these problems of teacher education, these ideas will be useful to educationist, Policy Makers, colleges and universities to work on the quality and standard of teacher education.